2011
DOI: 10.1097/aud.0b013e31821cc0df
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linguistic Comparison of Frequency-Following Responses to Voice Pitch in American and Chinese Neonates and Adults

Abstract: This study demonstrated an early maturation of voice-pitch processing in neonates starting from 1 to 3 days after birth and a significant effect of linguistic experience on the neural processing of voice pitch at the brainstem level. These findings provide a significant conceptual advancement and a basis for further examination of developmental maturation of subcortical representation of speech features, such as pitch, timing, and harmonics. These findings can also be used to help identify neonates at risk for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
80
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 62 publications
10
80
0
Order By: Relevance
“…The finding of robust F 0 representation in early infancy is consistent with that of Jeng et al (2011), and the gradual increase in high-frequency representation may arise from delayed maturation of phase locking to higher (compared to lower) frequency sounds, as was noted in auditory development studies in kittens (Brugge et al, 1978;Kettner et al, 1985). Although cochlear mechanics are presumed to be mature at birth (Abdala and Keefe, 2006), structures central to the cochlea may have a protracted course of development, and the time course of maturation of these structures may not be sequential.…”
Section: A Spectral Codingsupporting
confidence: 78%
See 1 more Smart Citation
“…The finding of robust F 0 representation in early infancy is consistent with that of Jeng et al (2011), and the gradual increase in high-frequency representation may arise from delayed maturation of phase locking to higher (compared to lower) frequency sounds, as was noted in auditory development studies in kittens (Brugge et al, 1978;Kettner et al, 1985). Although cochlear mechanics are presumed to be mature at birth (Abdala and Keefe, 2006), structures central to the cochlea may have a protracted course of development, and the time course of maturation of these structures may not be sequential.…”
Section: A Spectral Codingsupporting
confidence: 78%
“…The first study to record the FFR in newborn infants found adult-like amplitudes in response to a 500-Hz toneburst; however, peak latencies in response to lowfrequency stimuli were delayed compared to those of adults (Gardi et al, 1979). A more recent study using vowels found robust representation of the fundamental frequency (F 0 ) in neonates (Jeng et al, 2011). At this time, limited information is available regarding the representation of other speech features in the infant FFR (i.e., timing and spectral components).…”
Section: Introductionmentioning
confidence: 99%
“…Altogether these studies show that the neural attunement to native language takes place early during development and continues throughout the life-span, shaping the auditory system to become more efficient in processing phonemes that belong to the native language. Interestingly, Jeng et al (2011) have shown that this pattern of developmental change is also present at the subcortical level. Compared to Mandarin-speaking infants, adults have stronger subcortical pitch encoding, a lexically-relevant feature to discriminate Mandarin syllables.…”
Section: Introductionmentioning
confidence: 94%
“…Jeng, Schnabel Dickman, Montgomery-Reagan, Tong, Wu, et al, (2010) reported that the FFR recorded in young infants accurately refl ected the pitch contours of the acoustic stimuli. In a separate study (Jeng, Hu, Dickman, Montgomery-Reagan, Tong, Wu, et al, 2011), the response obtained from normal-hearing neonates showed an early maturation of voice-pitch processing in neonates 1 to 3 days after birth.…”
mentioning
confidence: 95%